Tolerance in the Communicative Culture of Modern Educational Manager - Sokol, Mariana (2021)
Cultural, racial, social, religious, ethnic heterogeneity of educational groups is a problem of modern education in the context of integration and globalization. This often becomes a reason for misunderstandings, sometimes aggression in the interaction of representatives of opposing worldviews, preferences or traditions. Tolerance in the communicative culture of the educational manager, activated at the level of management structures and broadcast vertically and horizontally through the education system through pedagogical teams to all categories of consumers of educational services, will be able to prevent this. The aim of the article is to outline the role of tolerance in the communicative culture of the modern education manager.  According to the purpose the following tasks of research have been defined: - to analyze sources of various branches of science and to find out meanings of basic concepts; - to outline the features of management in education in communication area; - to define its structure, establish relationships between components and develop a structural and semantic model of tolerance in the communicative culture of the education manager. The following research methods have been used to study the backgrounds of the problem: information, terminology, analysis, synthesis, methods of scientific research. The comparative-typological method has been used to compare, identify signs of similarities and differences between phenomena and facts Methods of forecasting and theoretical modeling have been used in the development of structural and semantic model. Systematization, classification and use of structural-functional analysis have been contributed to the generalization of the research results. Interdisciplinary approaches (sociocultural and multicultural) to the study of management, along with axiological, holistic, systemic, activity and synergetic are the methodological basis of the study. Methodological principles (synergetic, complementarity, activity (action and creative), interaction between the subjects of the educational process, convergence from the abstract to the concrete) have been applied. The scientific novelty of the research: - for the first time the meaning and value-semantic nature of tolerance in the communicative culture of an educational manager have been determined; - the determinants of educational management in the projection on communication have been clarified; - the interrelations between the components have been established and the possibilities for realization of tolerance in different directions of communicative culture have been revealed; - a structural and semantic model of tolerance in the communicative culture of the education manager has been developed. The main results of the study are the analysis of the source base from the standpoint of scientific approaches to various fields of knowledge (economics, sociology, psychology, pedagogy, management, culturology, etc.), which made it possible to identify a modern interpretation of "education management". The determinants of educational management as a component of social in the context of intangible, spiritual resource of education have been revealed. The similar and different characteristics of the managerial activity of the education manager and the pedagogical worker have been outlined. The essence, origin, structure, types and directions of functioning of communicative culture of the manager of education have been determined.